DIPLOMATIC MISSIONS OF SOVIET UKRAINE IN THE WORLD OF THE SECOND HALF OF THE XX CENTURY (Південний архів (історичні науки), 2022)
The purpose of the work. The article is devoted to the process of development of the Permanent Diplomatic Missions of Soviet Ukraine in the world of the second half of the XX century. Methods. The basis of methodological coverage of this article are general and special-historical methods, as well as scientific principles. Consideration of the structural features of the formation of the diplomatic apparatus of the Ukrainian Soviet Socialist Republic and the Permanent Missions of Soviet Ukraine is shown using the structural-functional method. The use of the scientific method of system analysis allowed to identify and trace the order of interrelation of the Permanent Missions of Ukraine with other diplomatic institutions. The application of the historical-genetic method allowed us to trace the process of formation of the bodies of Ukrainian diplomacy in the second half of the XX century. The method of source analysis was used during the study of archival materials. Coverage of the process of development of diplomatic missions of Soviet Ukraine in the second half of the XX century is associated with the use of problem-chronological and historicalcomparative method. The following scientific principles are used in the work, namely: historicism, continuity, integrity, systematics, objectivity. Results. The article analyzes the main aspects of the development and activity of the permanent diplomatic missions of Soviet Ukraine in the second half of the XX century. The process of cooperation of specialists of the diplomatic apparatus with the state bodies of Soviet Ukraine is shown. The process of changing the number of employees of the diplomatic corps of Soviet Ukraine in the second half of the XX century is traced. The peculiarities of the work of Ukrainian diplomats abroad are revealed. The process of interaction of Ukrainian diplomats with the Ukrainian diaspora is highlighted. The influence of the Ukrainian diplomatic corps on the formation and determination of the main directions of international policy of the Ukrainian Soviet Socialist Republic is reflected. Conclusions. It is proved that, despite the fact that Ukraine was part of the USSR, there was a gradual process of development of institutions of the Ukrainian diplomatic apparatus and Permanent Diplomatic Missions of Soviet Ukraine abroad in the second half of the XX century.
Keywords: UN, UNESCO, Soviet Union, diplomacy, international relations, international organization.